A retrospective study of the impact of health worker strikes on maternal and child health care utilization in western Kenya - Michael L. Scanlon; Lauren Y. Maldonado; Justus E. Ikemeri; Anjellah Jumah; Getrude Anusu; Jeffrey N. Bone; Sheilah Chelagat; Joann Chebet Keter; Laura Ruhl; Julia Songok; Astrid Christoffersen-Deb (BMC, 2021)
Abstract Background There have been dozens of strikes by health workers in Kenya in the past decade, but there are few studies of their impact on maternal and child health services and outcomes. We conducted a retrospective survey study to assess the impact of nationwide strikes by health workers in 2017 on utilization of maternal and child health services in western Kenya. Methods We utilized a parent study to enroll women who were pregnant in 2017 when there were prolonged strikes by health workers ("strike group") and women who were pregnant in 2018 when there were no major strikes ("control group"). Trained research assistants administered a close-ended survey to retrospectively collect demographic and pregnancy-related health utilization and outcomes data. Data were collected between March and July 2019. The primary outcomes of interest were antenatal care (ANC) visits, delivery location, and early child immunizations. Generalized estimating equations were used to estimate risk ratios between the strike and control groups, adjusting for socioeconomic status, health insurance status, and clustering. Adjusted risk ratios (ARR) were calculated with 95% confidence intervals (95%CI). Results Of 1341 women recruited in the parent study in 2017 (strike group), we re-consented 843 women (63%) to participate. Of 924 women recruited in the control arm of the parent study in 2018 (control group), we re-consented 728 women (79%). Women in the strike group were 17% less likely to attend at least four ANC visits during their pregnancy (ARR 0.83, 95%CI 0.74, 0.94) and 16% less likely to deliver in a health facility (ARR 0.84, 95%CI 0.76, 0.92) compared to women in the control group. Whether a child received their first oral polio vaccine did not differ significantly between groups, but children of women in the strike group received their vaccine significantly longer after birth (13 days versus 7 days, p = 0.002). Conclusion We found that women who were pregnant during nationwide strikes by health workers in 2017 were less likely to receive WHO-recommended maternal child health services. Strategies to maintain these services during strikes are urgently needed.